Maternal assault admissions are associated with increased risk of child protection involvement - Orr, Carol; Preen, David B; Glauert, Rebecca; O'Donnell, Melissa; Fisher, Colleen; Sims, Scott (International Journal of Population Data Science, 2018)
Introduction Almost half of Australian women assaulted by their partner have children in their care. Evidence suggests a link between children’s exposure to violence, and subsequent maltreatment allegations. However, this evidence is limited by small sample sizes. Linked administrative data present an opportunity to further investigate this sensitive topic. Objectives and Approach This study investigated the relationship between assaults on mothers and subsequent child maltreatment allegations. The sample included all live births in Western Australia from 1990 to 2009 (N=524,534) and their parents, with follow up to 2013. Linked administrative data on child maltreatment allegations and mothers’ assault-related hospital admissions were obtained. Multivariate Cox regression estimated the risk of maltreatment allegation following maternal assault admission. Adjusted and unadjusted hazard ratios (HR) and 95% confidence intervals (CI) were calculated for the risk of maltreatment allegation, and time (in months) between assault admission and the first maltreatment allegation. Results One in five children whose mother had an assault admission had a subsequent maltreatment allegation, increasing to more than one in three children when restricted to assault admissions in the prenatal period. More than half of the children who had a maltreatment allegation after their mother was admitted for assault were Aboriginal. After adjusting for covariates, children whose mother had an assault admission had two-fold increased risk of having a maltreatment allegation. The risk of maltreatment allegation was greatest in young children, 5.5-year-old (SD=4.6), when restricted to maternal assault admissions in the prenatal period the children were younger at 4-year-old (SD=4.1). The time from maternal assault admission to maltreatment allegation was around 12 months longer for Aboriginal children than for non-Aboriginal children. Conclusion/Implications Children of mothers who have been assaulted are at higher risk of child maltreatment allegation. Targeted early intervention is required for families with young children, and pregnant women experiencing violence. The time to maltreatment allegation for Aboriginal children warrants community developed culturally-safe partnerships between Aboriginal communities and government services.